PERTUMBUHAN HANJELI (Coix lacrima-jobi L.) PADA KEPADATAN POPULASI BERBEDA DI LAHAN SUB OPTIMAL - Nugraha Ramadhan; Rachmad Hersi Martinsyah; Indra Dwipa (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2020)
Research was conducted in Limau Manis, Padang City of West Sumatra. Theexperimental design used was a non-factorial randomized block design. Job’s tears used in this study is a cultivar of beras. The research objective was to determine the effect of various levels of population density on job’s tears growth in sub-optimal area. The density of the population used in this study is that A1 = 62,500 plants / ha (spacing of 40 x 40 cm), A2 = population of 50,000 plants / ha (spacing of 50 x 40 cm), A3 = 40,000 plants / ha (spacing 50 x 50 cm), A4 = 33,333 plants / ha (spacing 50 x 60 cm), A5 = 28,571 plants / ha (spacing 50 x 70 cm), A6 = 25,000 plants / ha (spacing 50 x 80 cm), A7 = 22,222 plants / ha (spacing 50 x 90 cm), and A8 = 20,000 plants / ha (spacing 50 x 100 cm). The results showed that the density of the plant population that was too dense had an effect on the decline in several growth components but showed the highest average ILD value. Whereas treatment with population density that was not too high or by using spacing that was tenuous gave the best effect on the variables of plant height, number of tillers and number of leaves. Further observations are needed to determine the effect of the treatment given on the yield components.